Răspuns :
1) = 60/12 - 8/12 - 3/12 + 36/12 - 180/12= (60-8-3+36-180)/12 = -95/12
2) = - 30/6 + 12/6 - 2/6 + 18/6 - 3/6 = (-30+12-2+18-3)/6 = - 5/6
3) = 60/40 + 50/40 - 56/40 - 41/40 = (60+50-56-41)/40 =13/40
4) = -40/60 - 45/60 +12/60 +60/60 = (-40-45+12+60)/60 = -13/60
5) = 4/5 -2/3 +3/5 = 12/15 - 10/15 + 9/15 = (12-10+9)/15 = 11/15
6) = 1/6 x 5/6 x (-1) = - 5/36
7) = 3/2 x (-3/8-5/8) = 3/2 x (-1) = -3/2
8) = 0,8 x 0,25 x (-2) = -0,4
2) = - 30/6 + 12/6 - 2/6 + 18/6 - 3/6 = (-30+12-2+18-3)/6 = - 5/6
3) = 60/40 + 50/40 - 56/40 - 41/40 = (60+50-56-41)/40 =13/40
4) = -40/60 - 45/60 +12/60 +60/60 = (-40-45+12+60)/60 = -13/60
5) = 4/5 -2/3 +3/5 = 12/15 - 10/15 + 9/15 = (12-10+9)/15 = 11/15
6) = 1/6 x 5/6 x (-1) = - 5/36
7) = 3/2 x (-3/8-5/8) = 3/2 x (-1) = -3/2
8) = 0,8 x 0,25 x (-2) = -0,4